Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To complete the truth table for the logical statement [tex]\( p \wedge \sim q \)[/tex], we analyze each combination of truth values for [tex]\( p \)[/tex] and [tex]\( q \)[/tex]. Recall that [tex]\( \sim q \)[/tex] represents the negation of [tex]\( q \)[/tex], and [tex]\( p \wedge \sim q \)[/tex] represents the logical AND between [tex]\( p \)[/tex] and [tex]\( \sim q \)[/tex].
We will calculate the values step by step for each row:
1. For [tex]\( p = \text{True} \)[/tex] and [tex]\( q = \text{True} \)[/tex]:
- [tex]\( \sim q = \text{False} \)[/tex]
- [tex]\( p \wedge \sim q = \text{True} \wedge \text{False} = \text{False} \)[/tex]
2. For [tex]\( p = \text{True} \)[/tex] and [tex]\( q = \text{False} \)[/tex]:
- [tex]\( \sim q = \text{True} \)[/tex]
- [tex]\( p \wedge \sim q = \text{True} \wedge \text{True} = \text{True} \)[/tex]
3. For [tex]\( p = \text{False} \)[/tex] and [tex]\( q = \text{True} \)[/tex]:
- [tex]\( \sim q = \text{False} \)[/tex]
- [tex]\( p \wedge \sim q = \text{False} \wedge \text{False} = \text{False} \)[/tex]
4. For [tex]\( p = \text{False} \)[/tex] and [tex]\( q = \text{False} \)[/tex]:
- [tex]\( \sim q = \text{True} \)[/tex]
- [tex]\( p \wedge \sim q = \text{False} \wedge \text{True} = \text{False} \)[/tex]
Now we compile these results into a truth table:
[tex]\[ \begin{tabular}{|c|c|c|c|} \hline $p$ & $q$ & $\sim q$ & $p \wedge \sim q$ \\ \hline \text{True} & \text{True} & \text{False} & \text{False} \\ \hline \text{True} & \text{False} & \text{True} & \text{True} \\ \hline \text{False} & \text{True} & \text{False} & \text{False} \\ \hline \text{False} & \text{False} & \text{True} & \text{False} \\ \hline \end{tabular} \][/tex]
This table fully describes the logical statement [tex]\( p \wedge \sim q \)[/tex] for all possible truth values of [tex]\( p \)[/tex] and [tex]\( q \)[/tex].
We will calculate the values step by step for each row:
1. For [tex]\( p = \text{True} \)[/tex] and [tex]\( q = \text{True} \)[/tex]:
- [tex]\( \sim q = \text{False} \)[/tex]
- [tex]\( p \wedge \sim q = \text{True} \wedge \text{False} = \text{False} \)[/tex]
2. For [tex]\( p = \text{True} \)[/tex] and [tex]\( q = \text{False} \)[/tex]:
- [tex]\( \sim q = \text{True} \)[/tex]
- [tex]\( p \wedge \sim q = \text{True} \wedge \text{True} = \text{True} \)[/tex]
3. For [tex]\( p = \text{False} \)[/tex] and [tex]\( q = \text{True} \)[/tex]:
- [tex]\( \sim q = \text{False} \)[/tex]
- [tex]\( p \wedge \sim q = \text{False} \wedge \text{False} = \text{False} \)[/tex]
4. For [tex]\( p = \text{False} \)[/tex] and [tex]\( q = \text{False} \)[/tex]:
- [tex]\( \sim q = \text{True} \)[/tex]
- [tex]\( p \wedge \sim q = \text{False} \wedge \text{True} = \text{False} \)[/tex]
Now we compile these results into a truth table:
[tex]\[ \begin{tabular}{|c|c|c|c|} \hline $p$ & $q$ & $\sim q$ & $p \wedge \sim q$ \\ \hline \text{True} & \text{True} & \text{False} & \text{False} \\ \hline \text{True} & \text{False} & \text{True} & \text{True} \\ \hline \text{False} & \text{True} & \text{False} & \text{False} \\ \hline \text{False} & \text{False} & \text{True} & \text{False} \\ \hline \end{tabular} \][/tex]
This table fully describes the logical statement [tex]\( p \wedge \sim q \)[/tex] for all possible truth values of [tex]\( p \)[/tex] and [tex]\( q \)[/tex].
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.